2017
DOI: 10.1021/acs.est.7b01153
|View full text |Cite
|
Sign up to set email alerts
|

Water Purification Using Functionalized Cellulosic Fibers with Nonleaching Bacteria Adsorbing Properties

Abstract: Portable purification systems are easy ways to obtain clean drinking water when there is no large-scale water treatment available. In this study, the potential to purify water using bacteria adsorbing cellulosic fibers, functionalized with polyelectrolytes according to the layer-by-layer method, is investigated. The adsorbed polyelectrolytes create a positive charge on the fiber surface that physically attracts and bonds with bacteria. Three types of cellulosic materials have been modified and tested for the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Other studies have shown a similar pattern when cellulose pulp is incubated with E. coli. One reason could be that the pulp serves as nutrient for the bacteria (Illergård et al 2012;Ottenhall et al 2017). The results of the leaching test confirm that CA leaching from the non-washed foams leading to a bacteria-reducing effect, but the excess CA is removed after washing.…”
Section: Bacterial Growth Inhibitionmentioning
confidence: 66%
“…Other studies have shown a similar pattern when cellulose pulp is incubated with E. coli. One reason could be that the pulp serves as nutrient for the bacteria (Illergård et al 2012;Ottenhall et al 2017). The results of the leaching test confirm that CA leaching from the non-washed foams leading to a bacteria-reducing effect, but the excess CA is removed after washing.…”
Section: Bacterial Growth Inhibitionmentioning
confidence: 66%
“…The usage of bio-based adsorbents, such as cellulose, in the removal of pollutants from water has gained increasing attention during recent years due to their potential wide availability, affordability, high adsorption capacity, regenerability, and lower sludge generation compared to many other processes [20]. In addition, chemical modification can further increase the adsorption capacity of, for instance, cellulosic adsorbents by introducing functional groups [21] or multilayer structures [22] to the material. Esterification using anhydrides, organic acids, or acid chlorides is an appealing approach to incorporating carboxylic acid functionalities into the cellulose backbone [21].…”
Section: Figurementioning
confidence: 99%
“…The filtration mode enables removal of particles that can host bacteria and interfere with the bacterial adsorption in the natural water samples and the filtration test shows an improvement in both time consumption and decontamination efficiency compared to previous studies using LbL-modified pulp fibres freely dispersed in natural water samples. 53…”
Section: Filtration Of Natural Water Samplesmentioning
confidence: 99%